Correlation between Electrical Properties and Potentiometric Response of CS-Clay Nanocomposite Membranes - M. Oviedo Mendoza; O. Arias de Fuentes; E. Prokhorov; G. Luna Barcenas; E. Padilla Ortega (Advances in Materials Science and Engineering)
The aim of this work is to study the relationship between electrical, structure, and potentiometric response to nitrate anions using Ion Selective Electrodes (ISE). These ISE are based on chitosan-montmorillonite nanocomposite membranes with different content of montmorillonite. Membrane properties have been studied using SEM, FTIR, and impedance spectroscopy measurements. With the advent of impedance spectroscopy one is allowed to obtain the DC conductivity dependence on montmorillonite concentration and the percolation threshold. Additionally, the potentiometric response to nitrate anions of ISE based on chitosan-clay nanocomposite has been investigated. It is shown that the properties and performance of these membrane electrodes depend upon the clay wt% and that the best sensitivity to nitrate ions (with detection limit 7 × 10−5 M) is obtained near the percolation concentration ca. 8 ± 2.5 wt% of clay. This observation is traceable to higher clay content (higher agglomeration) that tends to decrease the intercalation and absorption of the number of chitosan chains in the interlayer space of montmorillonite.